Pembayaran Bea Perolehan Hak Atas Tanah Dan Bangunan Pada Pembuatan Akta Hibah Wasiat - Paerunan, Olivia Gloria; Kuspraningrum, Emilda; Utomo, Setiyo (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Balikpapan City Regional Regulation Number 8 of 2023 expressly regulates that the obligation to pay BPHTB (Land and Building Rights Acquisition Fee) for bequests is payable when the grantee officially obtains rights to the inherited land and/or building. Based on research results, it shows that there are significant differences in interpretation among land deed making officials (PPAT) regarding this provision. Research findings reveal that there are differences in BPHTB payment practices carried out by PPAT. Some PPATs make payments at the beginning of the process, while others pay at the end. This difference reflects a misunderstanding among PPATs regarding when the tax liability is actually due.Purposes of the Research:  This research aims to analyze the implementation of BPHTB (Land and Building Rights Acquisition Fee) payments on will grants in Balikpapan City.Methods of the Research: This research uses socio-legal methods with primary data obtained directly through on-site interviews, as well as secondary data which is divided into three groups: primary legal materials (legislation), secondary legal materials (books, journals, papers, research results), and tertiary legal materials (law and Indonesian dictionaries). The choice of socio-legal method does not rule out support for the doctrinal approach studied in other laws and regulations.Results of the Research: The existence of differences in interpretation of the provisions when BPHTB is owed for testamentary grants in Balikpapan City Regional Regulation Number 8 of 2023 reflects a significant gap between written legal norms and implementation practices in the field. Misunderstanding by land deed officials regarding the timing of BPHTB payments indicates that there are obstacles in implementing the law, which can give rise to legal problems related to violation of norms.